(untitled) (Third Sector Social Economic Review, 2019)
The globalization of the world economy and increase in the international trade contributed to the development of transportation and communication infrastructure of Kazakhstan. In turn, this infrastructure helps to further the national interests of Kazakhstan by the exportation of transportation services. Logistics became a very crucial business in many countries. Logistics amount to the 20% to 30% of the GDP in developed countries. Market conditions demand high-quality transportation services complying with international standards. And these standards require continuous, reliable, fast, and low-cost service. The data obtained from this study is evaluated using time series analysis and regression analysis methods.